2013
DOI: 10.4236/ojacct.2013.23011
|View full text |Cite
|
Sign up to set email alerts
|

The Survey of Graduated Accounting Students’ Interest in Management Accounting: Evidence of Iran

Abstract: The purpose of this study is to investigate the perceptions of graduated accounting students in universities of Iran regarding their interest in management accounting versus other fields of accounting. Furthermore, this study determines the main factors that influence students' interest in management accounting. In order to compile the necessary information, a questionnaire was prepared and distributed to 75 graduated accounting students. The results show that accounting students prefer financial accounting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…This is supported by Porter and Woolley (2014) which found that extrinsic motivation is not as influential as intrinsic motivation. Influence by third parties also has an insignificant relationship with career path, which is in-line with past studies conducted by Wally (2013) and Hejazi and Bazrafshan (2013). According to Hejazi and Bazrafshan (2013), interest of family members and friends does not affect the students' own interest.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is supported by Porter and Woolley (2014) which found that extrinsic motivation is not as influential as intrinsic motivation. Influence by third parties also has an insignificant relationship with career path, which is in-line with past studies conducted by Wally (2013) and Hejazi and Bazrafshan (2013). According to Hejazi and Bazrafshan (2013), interest of family members and friends does not affect the students' own interest.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…A study carried out by Hejazi and Bazrafshan (2013) consisting of 75 questionnaires was used to survey the perception of graduate accounting students in universities of Iran regarding their interest in management accounting. The result showed that management accounting is less preferred to than financial accounting and auditing among the accounting students because financial accounting could provide them with better extrinsic motivation in terms of higher pay and better benefits.…”
Section: Extrinsic Motivationmentioning
confidence: 99%
“…In this regard, indicators of job market considerations include high demand for skilled human resources (Nguyen et. al, 2023), availability of good jobs along with numerous opportunities (Ng et (Hejazi and Bazrafshan, 2013). In this context, Bhat and Khan (2022) uncovered a significant correlation between job market considerations and the aspirations of accounting students to embark on a professional path.…”
Section: Job Market Considerationsmentioning
confidence: 99%
“…A person may work hard for an expected reward but not enjoy the task (Bainbridge, 2015). A study conducted by Hejazi and Bazrafshan (2013) with a group of accounting students showed that students chose their specialisation and career path based on extrinsic motivation. The students included in the study preferred financial accounting over management accounting as they believed that financial accountants receive a better pay package and other benefits.…”
Section: Motivating Factorsmentioning
confidence: 99%